2014 IEEE 33rd International Performance Computing and Communications Conference (IPCCC) 2014
DOI: 10.1109/pccc.2014.7017087
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing I/O patterns for the design of energy-efficient image servers

Abstract: Hard disks are one of the largest sources of power consumption in large-scale storage systems. The disk spin up/down technique has been shown to be an effective solution to this problem. Accordingly, the Open Compute Project (OCP) proposed a storage server for cold data, known as Cold Storage, to reduce power consumption using the spin-down technique in large-scale storage systems. With the aim of making effective use of Cold Storage, we characterize the power consumed by a hard disk in its various modes of op… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 12 publications
0
1
0
Order By: Relevance
“…In our previous study, we observed that 99.7% of all I/O requests arose from the most recent 8% of data [9] in the workload of a mobile messenger service. It exhibits more heavily skewed I/O patterns than similar applications [3], [6]- [8] do, in which small amounts of data cause most of the traffic. Because read requests cannot tolerate latency owing to a spin-up delay, it is difficult to use the cold storage tier directly for these applications.…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, we observed that 99.7% of all I/O requests arose from the most recent 8% of data [9] in the workload of a mobile messenger service. It exhibits more heavily skewed I/O patterns than similar applications [3], [6]- [8] do, in which small amounts of data cause most of the traffic. Because read requests cannot tolerate latency owing to a spin-up delay, it is difficult to use the cold storage tier directly for these applications.…”
Section: Introductionmentioning
confidence: 99%